2016
DOI: 10.1016/j.susc.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of hydrogen–water adsorption at terraces and steps of Pt(111) vicinal surface electrodes

Abstract: Abstract:In this work, the effect of the temperature on the adsorption states of Pt(111) vicinal surface electrodes in perchloric acid is studied through a thermodynamic analysis. The method allows calculating thermodynamic properties of the interface. In this framework, the concept of the generalized isotherm and the statistical thermodynamics description are applied to calculate formal entropies, enthalpies and Gibbs energies, ∆ 0 , of the adsorption processes at two-dimensional terraces and one-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…This happens with Pt(111) and Pt(100) in alkaline media [34]. Also, it should be noted that water interactions change with potential [35,36].…”
Section: Resultsmentioning
confidence: 95%
“…This happens with Pt(111) and Pt(100) in alkaline media [34]. Also, it should be noted that water interactions change with potential [35,36].…”
Section: Resultsmentioning
confidence: 95%
“…Some hypotheses have been proposed to explain this phenomenon, e.g. a mixed contribution of OH and O in this adsorption process [57], changes in the lateral interaction with pH [58] or the oxidative adsorption of water on the step edges [59]. To sum up, the electrochemical interface changes as the pH value is modified for all the studied orientations, and this can have consequences for the ORR activity.…”
Section: Pt(100) Pt(110) and Stepped Surfacesmentioning
confidence: 99%
“…[5] Recent work from Gómez-Marín et al suggested that near surface water may have a significant effect on the adsorption of hydrogen at platinum steps and that the changing electric field near the surface with pH may alter the structure and interaction of near surface water with adsorbed hydrogen. [19] Schwarz et al used DFT to suggest that water binds very strongly to platinum step sites, such that competitive adsorption of hydrogen and water occurs at low potentials. [20] They further show that a significant amount of charge can transfer to water adsorbed at step sites, which would give a nonunity electrosorption valency and explain a non-Nernstian shift with pH.…”
Section: Introductionmentioning
confidence: 99%